Experimental studies of the quantitative composition of corrosion products on the surface of reinforced concrete structures - K. I. Fomichenko; G. V. Volchanin; A. A. Kuznetsov; A. Yu. Kuzmenko (Омский научный вестник)
Reinforced concrete structures play a key role in modern infrastructure, however, corrosion of reinforcement poses a serious threat to their durability and safety. In this study, the sensitivity of a portable X-ray fluorescence analyzer (XRF) to corrosion products on the concrete surface is considered. The experiment was conducted using concrete samples containing varying amounts of iron hydroxide. The results showed that the FRA demonstrates high accuracy and reliability in detecting corrosion, which contributes to the improvement of diagnostic methods and maintenance of reinforced concrete structures.